2017
DOI: 10.1186/s12884-017-1585-0
|View full text |Cite
|
Sign up to set email alerts
|

Fever in pregnancy and the risk of congenital malformations: a cohort study

Abstract: BackgroundIn a variety of animal species, hyperthermia in pregnancy has been recognized as teratogenic. Hyperthermia interferes with protein synthesis via heat-shock proteins, which can entail membrane disruption, cell death, vascular disruption, and placental infarction. This can induce severe fetal malformations or death. Fever during pregnancy, especially during embryogenesis, has also been associated with congenital malformations in human offspring.The purpose of this large cohort study of clinically recog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 33 publications
1
43
0
5
Order By: Relevance
“…28 Among the 77 344 viable pregnancies with data collected at 16-29 weeks of pregnancy, in the 8321 pregnant women with a reported temperature above 38°C lasting 1-4 days in early pregnancy, compared with those without a fever in early pregnancy, the overall risk of fetal malformation was not increased (odds ratio [OR]=0.99 (95% CI, 0.88-1.12). 28 It has been reported that viral pneumonia in pregnant women is associated with an increased risk of preterm birth, fetal growth restriction (FGR), and perinatal mortality. 29 Based on nationwide populationbased data it was demonstrated that pregnant women with other viral pneumonias (n=1462) had an increased risk of preterm birth, FGR, and having a newborn with low birth weight and an Apgar score of less than 7 at 5 minutes, compared with those without pneumonia (n=7310).…”
Section: Fever Is Common In Covid-19-infected Patients Previous Datamentioning
confidence: 99%
“…28 Among the 77 344 viable pregnancies with data collected at 16-29 weeks of pregnancy, in the 8321 pregnant women with a reported temperature above 38°C lasting 1-4 days in early pregnancy, compared with those without a fever in early pregnancy, the overall risk of fetal malformation was not increased (odds ratio [OR]=0.99 (95% CI, 0.88-1.12). 28 It has been reported that viral pneumonia in pregnant women is associated with an increased risk of preterm birth, fetal growth restriction (FGR), and perinatal mortality. 29 Based on nationwide populationbased data it was demonstrated that pregnant women with other viral pneumonias (n=1462) had an increased risk of preterm birth, FGR, and having a newborn with low birth weight and an Apgar score of less than 7 at 5 minutes, compared with those without pneumonia (n=7310).…”
Section: Fever Is Common In Covid-19-infected Patients Previous Datamentioning
confidence: 99%
“…A retrospective review supported concerns for potential negative health impact associated with first trimester fever in humans [76]. To the contrary, a subsequent large-scale prospective study by the same authors concludes that there is no evidence that maternal fever during pregnancy induces congenital defects [77]. The latter finding corroborates reports that Concepts in Magnetic Resonance Part B 9 (noncontrast enhanced) MRI during pregnancy does not negatively impact childhood outcomes [78,79].…”
Section: Thermal Protection Of the Fetusmentioning
confidence: 63%
“…However, a recent study, including 80 321 pregnant women, reported that the rate of fever in early pregnancy was 10%, while the incidence of fetal malformation in this group was 3.7%. Among the 77 344 viable pregnancies with data collected at 16–29 weeks of gestation, in the 8321 pregnant women with a reported temperature > 38°C lasting 1–4 days in early pregnancy, compared to those without a fever in early pregnancy, the overall risk of fetal malformation was not increased (odds ratio = 0.99 (95% CI, 0.88–1.12)). Previous studies have reported no evidence of congenital infection with SARS‐CoV 61 , and currently there are no data on the risk of congenital malformation when COVID‐19 infection is acquired during the first or early second trimester of pregnancy.…”
Section: Perinatal Effect Of Covid‐19 Infectionmentioning
confidence: 88%
“…Previous data have demonstrated that maternal fever in early pregnancy can cause congenital structural abnormalities involving the neural tube, heart, kidney and other organs. However, a recent study, including 80 321 pregnant women, reported that the rate of fever in early pregnancy was 10%, while the incidence of fetal malformation in this group was 3.7%. Among the 77 344 viable pregnancies with data collected at 16–29 weeks of gestation, in the 8321 pregnant women with a reported temperature > 38°C lasting 1–4 days in early pregnancy, compared to those without a fever in early pregnancy, the overall risk of fetal malformation was not increased (odds ratio = 0.99 (95% CI, 0.88–1.12)).…”
Section: Perinatal Effect Of Covid‐19 Infectionmentioning
confidence: 91%